Study of Capacitive Coupling Sensor Fused With High Voltage XLPE Cable Joint - Xia, Rong; Zhao, Yang; Ouyang, Benhong; Wang, Yuli; Fang, Chunhua; Xu, Yao (Frontiers in Energy Research, 2022)
A capacitive coupling sensor for partial discharge detection with the fusion of high voltage XLPE cable joint is designed in this paper. The sensor is to address partial discharge signals leading to transmission attenuation and external interference causing poor field detection sensitivity. Firstly, a coaxial waveguide transmission model was established of high-frequency electrical signals in the body and joint. The result showed that the signal transmission attenuation was minimized while the sensor electrodes were closely attached to the outer semi-conductive layer of the body. Secondly, the equivalent circuit model was constructed of the capacitive coupling sensor fused with the 110kV straight passing joint. The specific installation location, main structure size, detection bandwidth, and sensitivity of the sensor in the joint area were determined, which was to maximize the coupling output signal amplitude and transfer function amplitude. Finally, a lightning surge voltage test was carried out with the integration of the fusion of the joint voltage thermal cycling. Simulation and measurement show: while the sensor is installed in the cable metal sleeve break and electrodes are closed to the overall semi-conductive layer, excellent performance for partial discharge detection in the frequency range of 1-300 MHz, with a sensitivity of 5pC.